Action anticipation in sports: A particular case of expert decision-making - Abreu, Ana Maria (Akademia Wychowania Fizycznego w Poznaniu)
A soccer player asks his girlfriend to marry him. To celebrate, they buy a red car. That day, during practice, the soccer player shoots to score a goal, unprecedentedly using his left foot, anticipating the goalkeeper’s next move. All of these actions result from social, consumer, and perceptual-motor decision-making (DM) processes. Although the soccer player might not be an expert decision maker in relationships or car deals, he is surely an expert when it comes to deciding how to score a goal. Not all decisions involve the same cognitive processes or neural underpinnings. Thus, when considering expert DM, it is crucial to clarify both the expertise domain and the decisional processes involved. Here, in this opinion mini-review, I present a brief overview of action anticipation (AA) in sports as a particular case of expert DM, making use of theories from economics to mathematical and clinical fields. Additionally, I discuss the cognitive and neural mechanisms subtending AA and show how certainty and saliency influence AA just like in other DM situations. Finally, I discuss how expert DM in the form of AA in sports can amount to a gut feeling, just like the gut feeling the soccer player needed to propose or buy a red car, instead of blue
Keywords: expert decision-making; action anticipation; level of certainty; familiarity